THE NATIONAL AND WORLD AXIOLOGICAL DIMENSIONS OF THE BESSARABIAN TRADITIONAL RUG - Varvara BUZILĂ (Academy of Sciences of Moldova, 2014)
The paper presents aspects of the traditional rug (scoarţa) that is the most representative type of rug of the folk art, being known and appreciated both within the Republic of Moldova and abroad. The author considers the conditions, the relationships and cultural forms that determined the emergence of this vivid domain of the folk art. Also are distinguished the specifi c marks of these creations in relation to the worldviews and the model of world that is characteristic for the traditional culture.